NGF promotes cell cycle progression by regulating D-type cyclins via PI3K/Akt and MAPK/Erk activation in human corneal epithelial cells - Hong, Jiaxu (Molecular Vision, 2012)
PURPOSE: Nerve growth factor (NGF) plays an important role in promoting the healing of corneal wounds. However, the molecular mechanism by which NGF functions is unknown. We investigated the possible effects of NGF on phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) and mitogen activated protein kinase (MAPK)/extracellular signal-regulated kinase (Erk) pathways and cell growth in human corneal epithelial cells (HCECs). METHODS: We examined the effect of NGF on cell cycle and proliferation in HCECs by flow cytometry and cell proliferation assay, respectively. The levels of D-type cyclins in NGF-treated HCECs were determined by western blot. The tyrosine kinase A (TrkA), PI3K/Akt and MAPK/Erk pathways were then checked in cells stimulated with NGF for different time periods or cells undergoing a dose-dependent treatment. Furthermore, HCECs were treated with pathway inhibitors, LY294002 or PD98059, to confirm NGF-induced activations. RESULTS: We found that NGF had a positive effect on the growth of HCECs, and D-type cyclins, and it was correlated with the percentage of the G(1) to S progression. We also observed a time-dependent and dose-dependent effect of NGF on the PI3K/Akt and MAPK/Erk pathways. Furthermore, NGF affected cell cycle progression of HCECs by regulating cyclin D through Akt and Erk activation upon treatment with the pathway inhibitors, LY294002 for Akt or PD98059 for Erk pathways. CONCLUSIONS: NGF stimulation could promote cell proliferation and cell cycle progression of HCECs by activation of cyclin D via the PI3K/Akt and MAPK/Erk signaling pathways.